Tax expenditure and the treatment of tax incentives for investment - Agustin Redonda; Santiago Diaz de Sarralde; Mark Hallerberg; Lise Johnson; Ariel Melamud; Ricardo Rozemberg; Jakob Schwab; Christian von Haldenwang (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Governments use tax expenditures to boost investment, innovation and employment. However, these schemes are largely opaque, costly and often ineffective in reaching their stated goals. They also frequently trigger unwanted side effects. In order to improve the performance of these tools, the authors present three concrete policy proposals: First, governments should increase transparency on tax benefits. G20 members should take the lead on this with frequent and comprehensive tax expenditure reports. Second, G20 governments should improve the design of tax incentives with the aim of minimizing the generation of windfall profits and negative spillover effects within and across (in particular, on poorer) countries. Third, governments should phase out tax expenditures that are environmentally harmful, including tax incentives for fossil fuels and other schemes that promote an unsustainable use of natural resources.
Keywords: H2; H87; N4; 330; tax expenditures; tax incentives; tax competition; investment; fossil fuel subsidies; G20